Zika virus-specific and orthoflavivirus-cross-reactive IgGs correlate with Zika virus seroneutralization depending on prior dengue virus infection. - Solène Marquine; Sébastien Briolant; Damien Claverie; Jessica Denis; Manon Geulen; Laurent Bosio; Bernard Tenebray; Sarah Attoumani; Annabelle Garnier; Laurence Cheutin; Gilda Grard; Bruno Coutard; et al. (PLoS Neglected Tropical Diseases, 2025)
Due to their expanding geographical distribution, many orthoflaviviruses co-circulate, increasing the likelihood of serial infections in individuals living in endemic areas. The consequences of such infection histories remain poorly understood. Using a cohort of Zika virus-infected patients, we modeled the kinetics of individual humoral responses to Zika virus (ZIKV) infection. We compared them between patients with and without prior orthoflavivirus exposure. We determined the day the humoral response was maximal and the maximum amplitude. We then determined the characteristic values of specific and cross-reactive responses for each individual, whether previously infected with dengue virus (DENV) or not. ZIKV neutralization by sera from ZIKV-infected individuals was mainly attributable to virus-specific antibodies. However, the same sera were able to neutralize all four DENV serotypes. ZIKV neutralization by sera from patients with prior DENV infection was mainly due to cross-reactive antibodies, which were also able to seroneutralize all four DENV serotypes. The de-novo antibody response induced against ZIKV was masked by the anamnestic response against DENV. Overall, our results show that the humoral response to an orthoflavivirus infection is influenced by the patient's history of prior orthologous orthoflavivirus infections.